The Transformative Power of Qur'anic Spiritual Education and Ruqyah Syariyyah in Nurturing Personal Character - Iskandar, Rudi (Al-Ilmu, 2024)
This research aims to explore how spiritual education based on the Qur'an and the practice of Ruqyah Shariyyah can contribute to the development of individual character with integrity and good morals. Using a library research approach, this study analyzes spiritual concepts in the Qur'an as well as the relevance of Ruqyah Syariyyah as a spiritual therapy that is beneficial for mental and spiritual health. An exploratory and explanatory approach is used to explore the moral values that can be obtained from spiritual education sourced from the Qur'an. The results of the study show that the combination of spiritual education of the Qur'an and Ruqyah Shariyyah can strengthen the values of faith, piety, and personal integrity. These values are considered an important foundation in building superior character, so this spiritual education not only has an impact on the moral aspect, but also on the mental health and spiritual well-being of individuals. Thus, this study emphasizes the importance of integrating spiritual education in character development to create individuals who are not only academically or professionally successful, but also have good integrity and morals.